The impact of constructivist methods on students' mathematical problem-solving - Blerina Çibukçiu (Discover Education)
Abstract This study examines the impact of constructivist methods on students' performance in mathematical problem-solving, which is a significant issue in contemporary educational research. Traditional teaching methods, which are often oriented towards rote learning and memorization, have limitations in increasing students' performance in solving mathematical problems. This research has analyzed how constructivist methods have a major impact on the third-graders' performance in solving these problems. In this research, a quantitative method with a quasi-experimental design was used. The sample consists of 143 third-graders, who were separated into two groups; the experimental group which used constructivist methods for solving mathematical problems and the controlled group which continued using traditional methods through standard teaching materials and relevant textbooks. All students were tested on mathematical-problem solving twice, once before the intervention and once after the intervention. Statistical analysis was performed using SPSS (version 27) and included Paired Samples T-test analysis. The results of the Paired Samples T-Test show a statistically important difference between the average scores before and after the use of constructivist methods in students' performance for solving mathematical problems. The average score in the pre-test was M = 39.77, while in the post-test it was M = 59.46, with an average difference of −19.69 and a statistical significance of p < 0.001. This study confirms that the use of constructivist methods in solving mathematical problems has a significant positive impact. These findings suggest that the integration of constructivist methods in teaching mathematics can be an effective strategy to help improve students' performance in solving mathematical problems.